Zamierzenia gospodarcze rolników-przedsiębiorców w kontekście ich współpracy z instytucjami lokalnymi - Zając, Dariusz (Economic Intentions of Farmers-Businessmen in the Context of their Co-Operation with Local Institutions, 2009)
The article presents economic intentions of farmers-businessmen in relation to the farm and agricultural production and nonagricultural activity in the context of their co-operation with local institutions. Research results show that the level of intensity of reports (co-operation) between these subjects has clear influence on the scale of the analyzed intentions. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 1, s. 903-911